Developmental Neuropathology and Neurodegeneration of Down Syndrome: Current Knowledge in Humans - Hasina, Zinnat; Wang, Nicole; Wang, Chi Chiu (Frontiers in Cell and Developmental Biology, 2022)
Down syndrome (DS) individuals suffer from developmental delay, intellectual disability and an early-onset of neurodegeneration Alzheimer’s like disease or precocious dementia due to an extra chromosome 21. Studying the changes in anatomical, cellular and molecular levels involved may help to understand the pathogenesis and develop target treatment, not just medical, also surgical, cell and gene therapy, etc., for individuals with DS. Here we aim to identify key neurodevelopmental manifestations, locate knowledge gaps, and try to build the molecular networks to better understand the mechanisms and clinical importance. We summarise current information of the neuropathology and neurodegeneration of the brain from conception to adulthood of DS foetuses and individuals at anatomical, cellular, and molecular levels in human. Understanding the alterations and characteristics in developing Down syndrome will help target treatment to improve the clinical outcomes. Early targeted intervention/therapy for the manifestations associated with DS in either the prenatal or the postnatal period may be useful to rescue the neuropathology and neurodegeneration in DS.